PENGARUH PROMOSI DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PEMBELIAN PRODUK PAKAIAN ERIGO: STUDI KASUS PADA KONSUMEN DI KECAMATAN WONOMERTO - Zakaria, Dwiky Febi; Lailiyah, Elliv Hidayatul (PT Naureen Digital Education, 2025)
This research focuses on evaluating the impact of promotion strategies and pricing on the level of customer satisfaction related to the acquisition of Erigo fashion products, with a specific focus on customers in the Wonomerto District area. The methodological approach applied is quantitative, involving the distribution of survey instruments to individuals who have purchased Erigo products. Data analysis was conducted using multiple regression techniques to measure the contribution of each independent variable. The study findings indicate that promotion has a positive and significant influence on consumer satisfaction, primarily driven by the level of information exposure and the quality of marketing communication content. Pricing was also demonstrated to have a substantial influence, with the alignment between monetary value and product quality being the main driver of satisfaction. In aggregate, both promotion and price show a strong contribution toward increasing consumer satisfaction